2021
DOI: 10.14202/vetworld.2021.499-507
|View full text |Cite
|
Sign up to set email alerts
|

Dietary effects of Garcinia kola seed meal on growth performance, hematology and serum biochemical parameters of weaned rabbits

Abstract: Background and Aim: Garcinia kola seed (GKS) is used to prevent and cure a number of gastric-related ailments. GKS contain a copious amount of polyphenols and can be utilized as a natural growth promoter in the nutrition of weaned rabbits. This study aimed to determine the dietary effects of GKS meal (GKSM) on the growth performance, hematology and serum biochemical parameters of weaned rabbits. Materials and Methods: GKS were dried and ground into powder. Thirty-two 8-week-old crossbred rabbits with an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Findings from various studies have shown that medicinal plants improve the productive performance of birds [1,2,3,4]), pullet chicks [5], rabbits [6,7], extends the shelf-life of stored meat products [8,9], in addition to their overall promise of enhancing public health.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from various studies have shown that medicinal plants improve the productive performance of birds [1,2,3,4]), pullet chicks [5], rabbits [6,7], extends the shelf-life of stored meat products [8,9], in addition to their overall promise of enhancing public health.…”
Section: Introductionmentioning
confidence: 99%